Longitudinal changes in total and regional body composition in patients with chronic obstructive pulmonary disease. Issue 9 (15th June 2021) - Machado, Felipe V. C.; Spruit, Martijn A.; Coenjaerds, Miranda; Pitta, Fabio; Reynaert, Niki L.; Franssen, Frits M. E.
Abstract: Background and objective: Low fat‐free mass (FFM) is common in patients with chronic obstructive pulmonary disease (COPD) and contributes to morbidity and mortality. Few studies have evaluated longitudinal changes in body composition in patients with COPD compared with non‐COPD controls. This study aimed to compare longitudinal changes in total and regional body composition between patients with COPD and non‐COPD controls and investigate predictors of changes in body composition in COPD. Methods: Patients with COPD and non‐COPD controls participating in the Individualized COPD Evaluation in relation to Ageing (ICE‐Age) study, a single‐centre, longitudinal, observational study, were included. Subjects were assessed at baseline and after 2 years of follow‐up. Among other procedures, body composition was measured by dual‐energy X‐ray absorptiometry scan. The number of exacerbations/hospitalizations 1 year before inclusion and during follow‐up were assessed in patients with COPD. Results: A total of 405 subjects were included (205 COPD, 87 smoking and 113 non‐smoking controls). Patients with COPD and smoking controls presented a significant decline in total FFM (mean [95% CI]: −1173 [−1527/−820] g and −486 [−816/−156] g, respectively) while body composition remained stable in non‐smoking controls. In patients with COPD, the decline in FFM was more pronounced in legs (−174 [−361/14] g) and trunk (−675 [−944/406] g) rather than in arms (54 [−19/126] g). The predictors of changes in total and regional FFM in patients with COPD were gender, number of previous hospitalizations, baseline values of FFM and BMI. Conclusion: Patients with COPD present a significant decline in FFM after 2 years of follow‐up, this decline is more pronounced in their legs and trunk. Abstract : Patients with chronic obstructive pulmonary disease (COPD) present a significant decline in total, leg and trunk low fat‐free mass (FFM), while arms FFM remains stable after 2 years of follow‐up. We identified a subgroup of patients with preserved FFM at baseline and history of previous hospitalizations that present greater decline in total and leg FFM compared to other patients with COPD. See related Editorial